2000
DOI: 10.1123/jsm.14.4.293
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and Change in Governance and Decision Making in National Sport Organizations: Institutional Explanations

Abstract: The purpose of this paper was to broaden the discussion and debate about the continuity and change in the governance and decision making of Canada's NSOs and to develop arguments that address why institutional theory provides a strong foundation for advancing our understanding and management of this continuity and change. First, the theoritical contributions of institutional theorists are discussed. This is followed by a critical evaluation of previous institutional perspectives on change in Canada's NSOs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
95
0
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(106 citation statements)
references
References 5 publications
1
95
0
10
Order By: Relevance
“…Previous research has focussed on the role of volunteer board members and the bureaucratisation of organisations (e.g., Auld & Godbey, 1998;Doherty & Chelladurai, 1999;Ferkins & Shilbury, 2010;Ferkins et al, 2009;Kikulis, 2000;Yeh & Taylor, 2008), but none to date has specifically focussed on the dynamics associated with adversarial and collaborative approaches to sport governance. Structure is also a unique attribute of this research question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has focussed on the role of volunteer board members and the bureaucratisation of organisations (e.g., Auld & Godbey, 1998;Doherty & Chelladurai, 1999;Ferkins & Shilbury, 2010;Ferkins et al, 2009;Kikulis, 2000;Yeh & Taylor, 2008), but none to date has specifically focussed on the dynamics associated with adversarial and collaborative approaches to sport governance. Structure is also a unique attribute of this research question.…”
Section: Discussionmentioning
confidence: 99%
“…To date, scholarly attention in relation to the governance of sport has tended to concentrate on organisational governance and, more specifically, governance of non-profit sport organisations (Hoye & Doherty, 2011). In research on sport governance to date, scholars have sought to establish the role of the board in sport organisations (Inglis, 1997;Shilbury, 2001;Yeh & Taylor, 2008;Yeh, Taylor, & Hoye, 2009); volunteer motivations for serving in the governing role (Cuskelly & Boag, 2001;Inglis, 1994); executive committee cohesion and decision-making (Doherty & Carron, 2003;Soares et al, 2010); board performance and structure (Hoye & Cuskelly, 2003a;Hoye & Doherty, 2011;Kikulis, 2000;Papadimitriou, 1999;Shilbury, 2001;Taylor & O'Sullivan, 2009); the shared leadership dynamic between the board and CEO (Auld & Godbey, 1998;De Barros, Barros, & Correia, 2007;Ferkins, Shilbury, & McDonald, 2009;Hoye, 2004Hoye, , 2006Hoye & Cuskelly, 2003b;Inglis, 1997;Schulz & Auld, 2006); and board strategic capability (Ferkins & Shilbury, 2010;Ferkins, Shilbury, & McDonald, 2005;Ferkins et al, 2009;Shilbury & Ferkins, 2011). These empirically derived themes evident within the literature have tended to emerge from countries such as Canada, Greece, Portugal, Spain, Taiwan, UK, Australia, and New Zealand where the sporting system is dominated by non-profit sport organisations.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have investigated changes in amateur sport organizations at the national level (Amis, Slack, & Hinings, 2004;Girginov & Sandanski, 2008;Hinings, Thibault, Slack, & Kikulis, 1996;Kikulis, 2000;Kikulis, Slack, & Hinings, 1992Stevens, 2006), and in professional sport franchises (Cousens, 1997;Cousens & Slack, 2005;O'Brien & Slack, 2004). A central theme guiding these investigations of organizational change is Hinings and Greenwood (1988) and Hinings's (1993, 1996) conception of archetypes (templates of organizing).…”
mentioning
confidence: 99%
“…National (sport) governing boards constitute the major decision making bodies and impact the ability to deliver services related to the primary activity of the organization (Hoye, 2002). In addition, such boards are increasingly (although not totally) similar to corporate boards, as nonprofit organizations are also moving toward professional management practices as they cope with a multiplicity and complexity of demands (Inglis, 1997;Kikulis, 2000). The change toward such professionalism may vary by sector and by the primary activity of an organization.…”
mentioning
confidence: 99%
“…Kikulis (2000) found that the shift to professional governance of national sport organizations was hindered by values that are deeply rooted in its traditions. Gender is one dynamic that is deeply embedded in the structure of and meanings assigned to sport.…”
mentioning
confidence: 99%